Dynamic Modeling of Workforce Planning for Infrastructure Projects - Sing, M.; Love, Peter; Edwards, D.; Liu, Henry (ASCE, 2016)
© 2016 American Society of Civil Engineers.Workforce planning (WP) for infrastructure projects provides a readily available pool of skilled labor that can deliver a nation's societal needs. However, achieving a robust and reliable workforce prediction is a constant challenge, as a variety of variables and factors must be considered. Despite various forecasting techniques and approaches being developed, government's worldwide continue to produce inaccurate forecasts and consequently fail to maintain the balanced workforce required to deliver infrastructure projects. To address this problem, a system dynamics (SD) model for the construction and civil engineering industry is developed, as traditional WP modeling approaches are static and unable to accommodate the changing complex dynamics that influence workforce supply and demand. The SD model is tested and used to formulate training policies that ensure workforce equilibrium and in turn, nurture sustainable infrastructure development.